Integrated valorization of industrial and municipal biomass wastes for green ammonia production: a circular bioeconomy approach - AlGhamdi, AbdulAziz; Taqvi, Syed Ali Ammar; Kazmi, Bilal; Naqvi, Salman Raza (Frontiers in Chemistry, 2025)
A sustainable production of ammonia using waste biomass is a new milestone to a low-carbon bioeconomy that is circular. This paper defines an integrated Aspen Plus model which integrates the steam gasification of paper mill sludge and municipal solid waste and the Haber-Bosch process to generate carbon-neutral green ammonia. The synthesis of thermochemical conversion and catalytic synthesis was optimized systematically by altering paper mill sludge feed ratio (20:80, 60:40, and 40:60 wt%), steam toward municipal solid waste ratio and pressures in the synthesis. The highest hydrogen yield (H2 = 0.4572) and heating value (7.82 MJ/Nm3) was obtained in the 60:40 blend at 800 °C and S/B = 0.025, whereas the highest NH3 mole fraction in the solution (0.9493) was obtained under 40:60 blend at 500 °C and 250 bar. The addition of cryogenic CO2 removal and water gas shift optimization greatly improved the purification of hydrogen and total carbon capture. The innovation of the work consists in the combined modelling structure that converts heterogeneous waste flows into a closed-loop, low-emission system of ammonia production, which has two advantages in the value of waste and the synthesis of renewable fertilizers. The results present an upscale able and ecologically friendly pathway to next-generation production of ammonia, between circular waste management and green chemical production.